Experimental performance analysis of a packaged R290 refrigeration unit retrofitted with R170 for ultra-low temperature freezing - Rodríguez-Criado, Juan Carlos; Expósito-Carrillo, José Antonio; Peris-Pérez, Bernardo; Domínguez-Muñoz, Fernando (Elsevier, 2021)
While the global refrigeration capacity installed in ultra-low temperature applications is considerably lower than in standard refrigeration, the interest in such systems has risen during the last months due to their emerging demand for the preservation of mRNA vaccines. Several theoretical studies can be found in the literature for ultra-low temperature applications. However, there is still a lack of reliable experimental data that may be used for the models validation and, thereby, to perform more rigorous investigations. In light of this, the present manuscript proposes an ultra-low temperature refrigeration unit based on an indirect cascade system, developed by retrofitting a standard low-temperature R290 packaged unit. In this investigation, firstly, the suitability of the original components is assessed and, then, the unit is experimentally tested within a wide range of operating conditions. Thereby, the system’s reliability is evaluated by assessing different parameters, such as discharge, condensing and evaporating temperatures and performance ratios. The main results showed a successful behaviour at the operating conditions tested, exhibiting a COP that ranged from 0.6 to 1.6 for cold room temperatures between -80 ºC and -65 ºC, respectively.
Analyse expérimentale des performances d'un groupe frigorifique monobloc au R290 converti au R170 pour la congélation à très basse température
https://openpolicyfinder.jisc.ac.uk/id/publication/12611
Keywords: Ingeniería térmica; Criogenia; Hidrocarburos; Hydrocarbons; Ethane; Propane; Retrofit; Ultra-low temperature